2013
DOI: 10.1016/j.neuron.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Mef2 Links the Drosophila Core Clock to Fas2, Neuronal Morphology, and Circadian Behavior

Abstract: Summary The transcription factor Mef2 regulates activity-dependent neuronal plasticity and morphology in mammals, and clock neurons are reported to experience activity-dependent circadian remodeling in Drosophila. We show here that Mef2 is required for this daily fasciculation-defasciculation cycle. Moreover, the master circadian transcription complex CLK/CYC directly regulates Mef2 transcription. ChIP-Chip analysis identified numerous Mef2 target genes implicated in neuronal plasticity, including the cell-adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
132
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(149 citation statements)
references
References 56 publications
(106 reference statements)
14
132
3
Order By: Relevance
“…Although it was recently reported that daily changes in s-LNv termini are a cycle of fasciculation and defasciculation (Sivachenko et al, 2013), we found that s-LNvs add and lose axonal material with a 24hr rhythm.…”
Section: Introductioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Although it was recently reported that daily changes in s-LNv termini are a cycle of fasciculation and defasciculation (Sivachenko et al, 2013), we found that s-LNvs add and lose axonal material with a 24hr rhythm.…”
Section: Introductioncontrasting
confidence: 76%
“…The approaches previously used to quantify the termini of s-LNv projections detected clear time of day differences (Fernandez et al, 2008; Sivachenko et al, 2013). However, these methods are laborious and limited to two dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis revealed that towards the end of the subjective night (CT22) PDF projections are significantly shorter than at the beginning (CT2) of the day (Figure 1C). These observations imply that mechanisms other than the proposed changes in the degree of fasciculation are recruited during circadian plasticity [8, 13]. To get a deeper insight into the nature of the phenomena we monitored the changes in brain explants kept in culture for 48 h after dissection.…”
Section: Resultsmentioning
confidence: 99%
“…This trend coincides with our observation of higher levels during the subjective morning, and lower levels at the beginning of the subjective night; however, we could not detect changes through the night, suggesting that, at least in clock neurons, there is a circadian rather than an homeostatic control of synaptic activity. Given that clock outputs are predominantly regulated at the transcriptional level [24], and that there is circadian regulation of MEF2, a transcription factor that turns on a program involved in structural remodeling [13], this correlation opens the provocative possibility that the circadian clock is controlling the ability of assembling novel synapses in particularly plastic neurons, which might become stabilized/recruited or otherwise pruned (disassembled), towards the end of the day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation